Perlindungan Hak Konstitusional Ekonomi Warga Negara Melalui Hak Paten di Indonesia - Alia Harumdani Widjaja; Winda Wijayanti; Rizkisyabana Yulistyaputri (Jurnal Konstitusi, 2020)
Cases of piracy against patents or trademarks are cases that often occur in Indonesia. Responding to these challenges, this study aims to find out how the legal protection of citizens economic constitutional laws through patents in Indonesia. This research is prescriptive legal research and was carried out using systematic literature review methods. The research data is sourced from rules and regulations in force in Indonesia, books, and articles from national and international journals that discuss patent rights. The researcher then analyzed the data collected in a descriptive qualitative manner. The results of this study indicate that the Indonesian government protects the constitutional rights of its citizens through patents by registering their work or products by the provisions in force in Indonesia. However, when the work or product is not registered, the product is not protected by law. For this reason, citizens who have works and products that are economically valuable that allow them to be reproduced are advised to register their products or works through patents.